Sustainable Livelihood Strategies of The Riverine Communities at Sadong Jaya, Sarawak, Malaysia : Role of Capital Assets - Wong, Swee Kiong; Tan, Su Jin; Regina Garai, Abdullah (Studies of Applied Economics, 2021)
The aim of this paper is to explore the role of capital assets in sustaining the livelihoods of the riverine communities with special focus on physical and human capitals. The study was carried out at Sadong Jaya, a sub-district under Asajaya District, Samarahan, Sarawak. It is located at the lower Sadong River lying in the Southwest of Sarawak in the Borneo Island. Due to the dynamic nature of the local environment with its unique geographical location prone to flash flood and monsoon flood, it is crucial to examine the role of physical and human capitals in affecting livelihood strategies adopted by the local communities. A mixed method approach encompassing exploratory study and descriptive analysis was adopted. Multistage sampling techniques were used to select 11 villages along the lower estuarine, middle estuarine and upper estuarine areas, followed by systematic sampling technique employed to select 243 heads of households for face-to-face interviews to find out their livelihood strategies and vulnerabilities faced by them. Data collection involved observation techniques, two FGDs and in-depth interviews with various stakeholders. The findings show that riverine communities at Sadong Jaya utilize diversified livelihood strategies by optimizing the use of capital assets available to sustain their livelihoods. Communities who are better equipped with an enhanced and diversified assets base are more resilient. The study found that infrastructures such as roads and bridges, water supply, drainage systems, watergates and education facilities enable the riverine communities to intensify and diversify economic activities, widen job opportunities and market opportunities. As accessibility to education and training facilities is made available to the locals through better connectivity facilitated by various physical infrastructure, more riverine communities are involved in non-agricultural economic activities and out-migrating to cities and abroad. The paper concludes that provision of basic physical and educational amenities is crucially imperative as a policy recommendation to ensure that the riverine communities are able to enhance their livelihoods strategies for uplifting their standards of living.